A phage weaponizes a satellite recombinase to subvert viral restriction. Issue 19 (19th October 2022) - Nguyen, Maria H T; Netter, Zoe; Angermeyer, Angus; Seed, Kimberley D
Abstract: Bacteria can acquire mobile genetic elements (MGEs) to combat infection by viruses (phages). Satellite viruses, including the PLEs (phage-inducible chromosomal island-like elements) in epidemic Vibrio cholerae, are MGEs that restrict phage replication to the benefit of their host bacterium. PLEs parasitize the lytic phage ICP1, unleashing multiple mechanisms to restrict phage replication and promote their own spread. In the arms race against PLE, ICP1 uses nucleases, including CRISPR-Cas, to destroy PLE's genome during infection. However, through an unknown CRISPR-independent mechanism, specific ICP1 isolates subvert restriction by PLE. Here, we discover ICP1-encoded Adi that counteracts PLE by exploiting the PLE's large serine recombinase (LSR), which normally mobilizes PLE in response to ICP1 infection. Unlike previously characterized ICP1-encoded anti-PLE mechanisms, Adi is not a nuclease itself but instead appears to modulate the activity of the LSR to promote destructive nuclease activity at the LSR's specific attachment site, attP . The PLE LSR, its catalytic activity, and attP are additionally sufficient to sensitize a PLE encoding a resistant variant of the recombination module to Adi activity. This work highlights a unique type of adaptation arising from inter-genome conflicts, in which the intended activity of a protein can be weaponized to overcome the antagonizing genome.